Different Types of Myotonic Muscle Disorders at Dhaka Medical Collage Hospital - Daisy, Selina; Sayeed, SM Nurul Momin; Mohammad, Quazi Deen; Hossain, Sakhawat; Habib, Mansur; Hoque, Azharul; Alam, Badrul; Haque, Badrul (Journal of Bangladesh College of Physicians and Surgeons, 2010)
After introduction of EMG at Dhaka Medical Collage on January 01, 2006 , a total of 329 cases referred to EMG laboratory for electrophysiologic evaluation over a period of one & half year (January 01, 2006 to June 30, 2007). Among them, 45 cases diagnosed as different types of myopathies. Among these cases, eleven (11) diagnosed as myotonic muscle disorders. The subtypes of myotonic muscle disorders were 1. Myotonic Dystrophy. 2. Proximal Myotonic Myopathy. 3. Myotonia Congenita DOI: 10.3329/jbcps.v26i3.4194 J Bangladesh Coll Phys Surg 2008; 26: 121-123